2015
DOI: 10.1111/ijd.12768
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of specific anti‐desmoglein 1 and 3 enzyme‐linked immunoassay and indirect immunofluorescence in the evaluation of pemphigus activity

Abstract: Therapeutic strategies should not be based exclusively on anti-Dsg antibody values. Anti-Dsg1 antibodies showed a closer relationship with skin activity than IIF, while anti-Dsg3 antibodies showed a relationship with mucosal activity similar to the IIF test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…While, anti-Dsg-3 antibody level showed no difference during treatment period and anti-Dsg-1 antibody level only presented significant decreasing 6 weeks after treatment. It is inconsistent with other studies, which demonstrated that decrease in anti-Dsg-1 antibody and anti-Dsg-3 antibody level is parallel with the clinical improvement in pemphigus patients ( Barnadas et al, 2015 ). While this inconsistency probably due to the longer follow-up period in other studies.…”
Section: Discussioncontrasting
confidence: 83%
“…While, anti-Dsg-3 antibody level showed no difference during treatment period and anti-Dsg-1 antibody level only presented significant decreasing 6 weeks after treatment. It is inconsistent with other studies, which demonstrated that decrease in anti-Dsg-1 antibody and anti-Dsg-3 antibody level is parallel with the clinical improvement in pemphigus patients ( Barnadas et al, 2015 ). While this inconsistency probably due to the longer follow-up period in other studies.…”
Section: Discussioncontrasting
confidence: 83%
“…The relatively recent development of IIF and ELISA tests have further facilitated the diagnosis of autoimmune bullous dermatoses and comparable sensitivities and specificities have been reported (PV: 75-100%, 91.8-100%; PF: 67-100% for IIF; Dsg3: 81-100%, 94-100%; Dsg1: 69-100%, 61.1-100% for ELISA; Amagai et al, 1999 , Amagai et al, 1999 , Barnadas et al, 2015 , Bracke et al, 2013 , Chiang et al, 2015 , Cozzani et al, 1994 , Daneshpazhooh et al, 2007 , Daneshpazhooh et al, 2014 , Hallaji et al, 2010 , Harman et al, 2000 , Harman et al, 2000 , Ishii et al, 1997 , Jiao and Bystryn, 1997 , Khandpur et al, 2010 , Mortazavi et al, 2015 , Schmidt et al, 2010 , Sharma et al, 2006 , Tampoia et al, 2012 , van Beek et al, 2012 , van Beek et al, 2017 , Zagorodniuk et al, 2005 ). An international, multicenter study further demonstrated a high diagnostic agreement of 93.6% (Cohen k value, 0.95) between DIF results and multivariant ELISA testing for patients with pemphigus ( van Beek et al, 2017 ).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, Barnadas et al (2015) reported inaccuracies in anti-Dsg1 and Dsg3 ELISA values when titer levels exceeded 150 U/mL, which is possibly due to the saturation of the system and results in artefactually low scores. Additionally, later studies have demonstrated that a semi-quantitative analysis can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect immunofluorescence Autoimmune Bullous Diseases(IIF) examination, using a substrate of normal human skin or monkey esophagus, shows circulating antiepithelial IgG and lace-like deposition [2,4,5,12]. Enzyme-linked immunosorbent assay (ELISA) is also available in detecting antigens of PV and serves as a tool for assessing the disease severity [44,45]. Target antigens identified in PV are Dsg1 (with a molecular weight (MW) of 165 kD) and Dsg3 (MW-130 kD) [2][3][4][5]9].…”
Section: Immunopathology and Target Antigensmentioning
confidence: 99%